Bacterial Profile and Antibiotic Susceptibility Patterns of Urinary Tract Infection Among Children in Karbala Teaching Hospital: Bacterial Profile and Antibiotic Susceptibility Patterns of Urinary Tract Infection - Masar AL-Mousawi; Ameer Hanoon; Alaa Jasim; Alaa Alattab; Karar Musafer; Zahraa Abdulzahraa (Journal of Tropical Life Science, 2023)
Urinary tract infections (UTIs) are common diseases in pediatric age groups. The emergence of bacterial strains that exhibit resistance to specific antimicrobial agents has led to several therapeutic challenges. This study aimed to evaluate the frequency and antimicrobial susceptibility patterns of common types of bacteria isolated from urine samples of patients with urinary tract infections in Karbala Teaching Hospital for Children. The study was conducted between September 2021 and January 2022. The susceptibilities of antimicrobial agents were determined using the Kirby-Bauer disk diffusion technique. Positive cultures from 56 patients were included in the analysis. Escherichia coli and Proteus spp. were the most common organisms identified in pediatric patients suspected of a UTI (50% and 14.3%, respectively), while Raoutella ornithimolytics and Enterobacter sp. represented 7.14%. Other bacteria like Pseudomonas aeruginosa, Staphylococcus saprophyticus, Acinetobacter baumannii, Serratia spp., and Kluyvera spp. represented 3.6%. The sensitivity of E. coli isolates to imipenem, amikacin, and chloramphenicol were 92.9%, 85.7%, and 78.6%, respectively. Proteus spp. isolates solely exhibited susceptibility to amikacin and nalidixic acid. The current study concluded that E. coli was the most frequently arising underlying pathogen UTI in pediatric patients. In this clinical setting, the organisms identified exhibited high susceptibility to imipenem, amikacin, and chloramphenicol.